Comparative assessment of Cochrane’s ROB and ROB2 in dentistry trials: a meta-research study - João Viana; Vanessa Machado; Luís Proença; Leandro Chambrone; José João Mendes; João Botelho (Systematic Reviews)
Abstract This meta-research study aimed to compare the assessment of Cochrane’s Risk of Bias (RoB) and RoB2 tools in dentistry trials. A sample 150 in vivo randomized clinical trials published between 2020 and 2022 was randomly selected from PubMed/Medline, Scopus, and EMBASE databases (50 per year). For each study, the impact factor, journal quartile, adherence to CONSORT guidelines, date information availability, and study model were recorded. The results showed that 33.3% of the studies were categorized as low risk of bias by both RoB and RoB2. However, 29.6% of the studies classified as low risk by RoB were downgraded to some concerns in RoB2, and 37% were downgraded to high risk. In the some concerns category, 25.9% were upgraded to low risk, 37% remained constant, and 37% were downgraded to high risk in RoB2. Among the high risk studies, 14.6% were upgraded to low risk, 26% to some concerns, and 59.4% remained constant in RoB2. The level of agreement between RoB and RoB2 was found to be low for dental studies. These findings highlight the differences between the two tools and the potential impact on the synthesis of evidence and decision-making processes in dental research.